2021
DOI: 10.1002/jcla.23926
|View full text |Cite
|
Sign up to set email alerts
|

Levels of SERPIN family proteins in peri‐implant crevicular fluid in patients with peri‐implantitis

Abstract: Purpose Serine protease inhibitors (SERPINs) family has been discovered in many disorders with proteolysis mechanisms. Our study determined the SERPINBs protein expression via public‐based GEO databases and further validated by peri‐implant crevicular fluid (PICF) of peri‐implantitis patients and healthy recruiters. Methods This study is a retrospective analysis. A total of 123 participants of Fujian Medical University Fujian Stomatological Hospital, consisting of 58 cases of peri‐implantitis and 65 samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…A superfamily of protease inhibitors (SERPINB) is responsible for many inflammatory processes, and it is also found overexpressed in oral squamous cell carcinoma . A recent report has validated the up-regulated expression of SERPINBs in peri-implant crevicular fluid samples from patients diagnosed with peri-implantitis (inflammatory disease around dental implants in the oral cavity) . The association between overexpressed SERPINBs and increased IL-6 and TNF-α as pro-inflammatory cytokine production could suggest an indirect effect of isolated salivary proteins on deleterious cell function.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A superfamily of protease inhibitors (SERPINB) is responsible for many inflammatory processes, and it is also found overexpressed in oral squamous cell carcinoma . A recent report has validated the up-regulated expression of SERPINBs in peri-implant crevicular fluid samples from patients diagnosed with peri-implantitis (inflammatory disease around dental implants in the oral cavity) . The association between overexpressed SERPINBs and increased IL-6 and TNF-α as pro-inflammatory cytokine production could suggest an indirect effect of isolated salivary proteins on deleterious cell function.…”
Section: Discussionmentioning
confidence: 89%
“…63 A recent report has validated the up-regulated expression of SERPINBs in peri-implant crevicular fluid samples from patients diagnosed with peri-implantitis (inflammatory disease around dental implants in the oral cavity). 64 The association between overexpressed SERPINBs and increased IL-6 and TNF-α as pro-inflammatory cytokine production could suggest an indirect effect of isolated salivary proteins on deleterious cell function. Although the causes and consequences involved in the dysregulation of salivary proteins in soft tissue cells remain unknown, our confocal image has distinctly provided insights regarding the impact of exclusive proteins of pasteurized saliva on cell morphology and viability, which must be further explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In peri-implantitis, however, the concentrations of IL-6 in peri-implant cervical fluid (PICF) are more substantial. Subsequent research confirms this trend, with some studies extending the comparisons to peri-implant mucositis [25,[35][36][37][38][39][40][41][42][43]. Among all the research found, only one study did not find distinctively elevated levels of IL-6.…”
Section: Il-1β (+3953/+3954)mentioning
confidence: 85%
“…Tumor Necrosis Factor α (TNFα) TNFα is the third main inflammatory cytokine one can detect in inflamed tissues. Peri-implant tissues are characterized by overall elevated levels of TNFα, both in soft and hard tissues, compared to healthy implants [30,36,41,43,46,50]. Upon comparing the concentrations of TNFα between periodontitis and peri-implantitis, greater concentrations were noticed in the peri-implantitis group [40].…”
Section: Interleukin-1β (Il-1β)mentioning
confidence: 99%
See 1 more Smart Citation